2003
DOI: 10.1063/1.1591070
|View full text |Cite
|
Sign up to set email alerts
|

Intense vortex pinning enhanced by semicrystalline defect traps in self-aligned nanostructured MgB2

Abstract: In this work, we report the discovery of a vortex pinning source: semicrystalline defect wells in self-aligned nanostructured MgB2. It is demonstrated that these aperiodic regions trap numerous crystal defects migrating along nanodomain boundaries during self-alignment and act as intense vortex pinning centers that significantly enhance the high-field performance of MgB2. This suggests that the density of trapped defects in the wells is much greater than that found in other vortex pinning sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 12 publications
(9 reference statements)
2
13
0
Order By: Relevance
“…21 The majority of nanodomains have a rectangular shape with a domain size of about 2 -4 nm. The domain boundaries trap numerous defects to form nanodefect wells and release the strain caused by the rotation of nanodomains, as reported by Li et al 21 This nanodomain structure may be the result of a small proportion of C substituted for B. In our recent work, we found that C substitution indeed improved flux pinning while also depressing T c .…”
Section: Resultsmentioning
confidence: 99%
“…21 The majority of nanodomains have a rectangular shape with a domain size of about 2 -4 nm. The domain boundaries trap numerous defects to form nanodefect wells and release the strain caused by the rotation of nanodomains, as reported by Li et al 21 This nanodomain structure may be the result of a small proportion of C substituted for B. In our recent work, we found that C substitution indeed improved flux pinning while also depressing T c .…”
Section: Resultsmentioning
confidence: 99%
“…For the readers' convenience, each section starts with key points synopsizing discussions. tivity, 35,36 thermal stability, 37,38 wettability, 39,40 water and ice skin supersolidity, 41,42 etc.…”
Section: Scopementioning
confidence: 99%
“…The dark-field images and corresponding bright-field images of one of the nanodomains for sample A are shown in Figs. 11 The interface between the domain and the surrounding matrix is also free of secondary phases, as evidenced by vanishing of the domain-wall contrast, as the sample is tilted.…”
Section: Clean Crystalline Interfacesmentioning
confidence: 99%
“…1, with evenly spaced dislocations and the coherent domain boundaries of the "MgB 2 precipitates" found within the MgB 2 grains) (Figs. Crystalline B (99.95 wt% purity 11 B) and 99.999 wt% pure crystalline Mg flakes were used for the synthesis, suggesting that the amorphous phase is a reaction product, rather than a residue from the starting materials. However, some boundaries, which were faceted along low index planes, were wetted by amorphous phase.…”
Section: A Grain Boundary and Interface Structuresmentioning
confidence: 99%